The rise and fall of the New Deal order, 1930-1980 - Fraser, Steve, 1945-; Gerstle, Gary, 1954- (Princeton University Press, 1989)
The 10 essays in this book probe the underlying economic, social, and cultural dynamics of the Roosevelt revolution, analyze the durability of the New Deal coalition through the mid-1960s, and uncover the racial, class, and cultural fissures that led to its disintegration. The contributors answer such questions as: How did the Democratic Party accommodate both poor workers and wealthy capitalists: Why did the labor question lose its importance in American politics as soon as the movement achieved political power? Why did economic abundance generate political and cultural conservatism in the 1950s but radicalism in the 1960s? ISBN 0-691-04761-8: $25.00.